Reverse -Magic Graphoidal on Circle Related Graphs - Thomas, Mini.S; T.K, Mathew Varkey (International Journal of Computer Sciences and Engineering, 2025)
Let G=(V,E) be a graph and let ψ be a graphoidal cover of G. Define f^* in ψ with f *(P) = f(v1)+ f(vn)+∑_(i=1)^(n-1)▒〖f(v_i v_(i+1) )=〗 k is a constant, where f^* is the induced labeling on . Then, we say that G admits  - magic graphoidal total labeling of G. In this paper we formulated a reverse process of magic graphoidal called reverse-magic graphoidal labeling and proved C_n, Parachute W_(n,2), Armed Crown C_n Ѳ P_n , K_(1,n)×K_2 are reverse magic graphoidal.